(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تمت في هذا البحث دراسة الامتصاصية لبعض المعادن (الألمنيوم, الحديد, النحاس, التوتياء) المتوفرة في السوق المحلية, حيث يمكن استخدام هذه المعادن كسطوح ماصة absorber plate في السخانات الشمسية ولتصميم الحساسات الحرارية . قمنا بإجراء هذه الدراسة في المخبر أولاً (باستخدام منبعين للضوء استطاعة الأول 100 واط واستطاعة الثاني 30 واط ), وثانياً في الوسط الخارجي باستخدام الإشعاع الشمسي المباشر. و يوفر بحثنا هذا معلومات هامة يمكن الاستفادة منها في تحسين مردود السخانات الشمسية باستخدام السطوح الماصة التي لها أعلى امتصاصية. كما قمنا بدراسة العلاقة بين هذه الامتصاصية والعدد الذري للمعادن المدروسة, حيث أظهرت هذه الدراسة أن الطاقة الممتصة بوساطة هذه المعادن تزداد بازدياد عددها الذري. In this research we have studied the absorbance of some metals (aluminum, iron, copper, zinc) available in the local market, where these metals can be used as absorber plate in the manufacture of solar water heaters and thermal sensors . we conducted this study in the laboratory , first (using tow light sources, 100W and 30 W), and Second in the external medium using direct solar radiation. And our research provides important information that could be used in improving the efficiency of solar water heaters using absorbent surfaces that has a higher absorbency. We have also studied the relationship between the absorbance and the atomic number of the studied metals. This study showed that the absorbed energy by these metals increase with their atomic number Z.